2015
DOI: 10.1007/s00540-015-2016-x
|View full text |Cite
|
Sign up to set email alerts
|

Laryngoscopy facilitates successful i-gel insertion by novice doctors: a prospective randomized controlled trial

Abstract: Our results suggest that laryngoscopy facilitates i-gel insertion by novice doctors, as reflected in the rate of successful insertions, higher sealing pressure, and lower subjective difficulty of insertion in anesthetized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…After obtaining written informed consent, 40 patients aged 20 to 75 years who were to undergo general anesthesia in a supine position were randomly assigned (envelope method) to one of two groups: intubation by a tracheal tube with the HVLP cuff (HVLP group, 20 patients) or the taper-shaped cuff (Taper group, 20 patients). Exclusion criteria were morbid obesity defined by a body mass index >35, cervical disease or cervical movement restriction, gastroesophageal reflux, previous upper abdominal surgery, and a recent (within seven days) history of upper respiratory tract infection [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…After obtaining written informed consent, 40 patients aged 20 to 75 years who were to undergo general anesthesia in a supine position were randomly assigned (envelope method) to one of two groups: intubation by a tracheal tube with the HVLP cuff (HVLP group, 20 patients) or the taper-shaped cuff (Taper group, 20 patients). Exclusion criteria were morbid obesity defined by a body mass index >35, cervical disease or cervical movement restriction, gastroesophageal reflux, previous upper abdominal surgery, and a recent (within seven days) history of upper respiratory tract infection [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, supraglottic airway management, such as use of the i-gel, minimizes the risk of glottis damage, although there is a risk of ventilation failure due to malpositioning in the lateral position. In the present case, we inserted the i-gel under guidance of the McGRATH MAC videolaryngoscope to minimize collisions with the glottis [3], and mechanical ventilation was performed uneventfully as a result.…”
Section: Discussionmentioning
confidence: 99%
“…Our study additionally demonstrated that the tracheal tube introducer can be applied to cases of difficult ProSeal insertion. To facilitate positioning of the tracheal tube introducer into the esophagus, we used the McGRATH videolaryngoscope, which provided a good laryngeal view [3,4]. Use of the videolaryngoscope prevented unnecessary injuries and migration of the introducer.…”
Section: Discussionmentioning
confidence: 99%